Worker Alienation as a Moderator of the Job Quality-Job Satisfaction Relationship: The Case of Racial Differences - Vecchio, Robert P. (Academy of Management Journal, 1980)
The study, a test of the individual differences moderator hypothesis, used data from six national samples and incorporated a full range of job quality and a heretofore unexplored index of "worker alienation from mainstream work norms" (i.e., employee race). Evidence was found that the moderator hypothesis is descriptively valid, but additional complexities must be considered before firm conclusions are drawn.